EFFECTIVENESS OF DEVELOPMENT PROGRAMME IMPLEMENTATION MINAPOLITAN SEAWEED CULTIVATION IN DISTRICT PINRANG - Beryaldi Agam (JURNAL MINA SAINS, 2019)
Minapolitan program policy implementation should be carried out effectively in accordance with predetermined rules because it determines the success of a program. This study aimed to analyze the effectiveness of the implementation of the development program Minapolitan seaweed farming in Pinrang in terms of output and outcome Program. This type of research is research survey using descriptive data analysis of qualitative and quantitative through the analysis of the Likert scale (the assessment criteria very effective = 4, effective = 3, less effective = 2, and Effective = 1) to measure the level of effectiveness by looking at the achievements of the program output minapolitan namely the addition of facilities, infrastructure additions, business improvement, increase in the fishing industry, the increased contribution of all stakeholders, improving the quality and quantity of human resources, and increase the number of skilled group. Outcome programs, namely the increase in production and marketing, income generation, capital raising and investment, and employment. Based on the results showed that the accumulation table computed values overall average variable rate of effectiveness of program implementation minapolitan is 2.33 Effective in the category. However, some indicator variables that are in the category of effective unless the variable addition of the fishing industry is in the category of less effective with 1.73 value it is necessary to increase the efficiency, effectiveness, and accountability of program performance minapolitan all levels based on the rules that apply. Keywords: Effectiveness, Implementation, Minapolitan Program, Seaweed